ANALISIS PENGENDALIAN INTERN ASET TETAP PADA PT. HASJRAT MULTIFINANCE CABANG MANADO - Budiman, Erwin; Elim, Inggriani (Universitas Sam Ratulangi, 2016)
Fixed assets have a very important role for any company. Hence the need for the internal control system of fixed assets aimed at ensuring the security of company property, checking the accuracy and correctness of accounting data, to help encourage compliance policy leaders are set beforehand. This study aims to determine the application of the internal control structure of fixed assets at PT. Hasjrat Multifinance Branch Manado. Data analysis method used is descriptive method is a method to describe or analyze the results of the study but not used to make broader conclusions. The data used is qualitative data with secondary data sources, data collection techniques done is documentation and interview techniques. The results of research by the author, on the analysis of internal control of fixed assets at PT. Hasjrat Multifinance Branch Manado, concluded that internal control has not been effectively implemented. It can be seen from the dual function of labor between the accounting and finance are done by one person, the absence of an audit committee that controls the activity of the company, is not implemented training programs for employees, never done a physical examination once a year for fixed assets, there is no separation capital expenditures (capex) and revenue expenditure as well as the useful life of fixed assets is up is not the removal of fixed assets.